Оптимізація 3d моделей для ігрових рушіїв - Манченко, А. В. (ХНУРЕ, 2024)
Over the past decades, the computing power of computers has grown rapid ly. Thanks to this, the modern gaming industry has the opportunity to create graphics that are close to reality, and in recent years projects have appeared whose graphics can hardly be distinguished from realism. However, even with current capabilities, optimization of 3D models should be observed when creating them, since without it will be impossible to fit many objects into one game, as well as perform high-quality animation. This work will describe ways to optimize 3D models for successful export to game engines.
Keywords: ігрові рушії